COMPARISON OF THREE DIFFERENT TECHNIQUES OF GENE TRANSFER IN HUMPBACK GROUPER ( ) CROMILEPTES ALTIVELIS - KOMAR SUMANTADINATA; SLAMET SUBYAKTO; ALIMUDDIN; RUSTIDJA; M. SASMITO JATI; IRVAN FAIZAL; RATU SITI ALIAH; GEMI TRIASTUTIK (SEAMEO BIOTROP, 2011)
Humpback grouper is one of the most cultured fishes in Asia, including Indonesia. Themain problemfaced by humpback culture is its slow growth rate.One of themethods that willbe more effective and efficient to solve the problem is using transgenic technique. This studywas conducted to determine the effectiveness of transfection,microinjection and electroporationtechniques on gene transfer in humpback grouper. transfection was performed byincubating sperm to the foreign DNA (pktBP-ktGH gene construct)-transfectant complexsolution, while was by injecting those complex solution into testis of mature males.Microinjection was conducted in 2-4 cell stage embryos using 25 Î¼g/ml of foreign DNAsolution, and duration of injection was 1, 2 and 3 seconds. Electroporation by 50 V, 30 ms ofpulse length, 5 of pulse number and 0.1 of pulse interval was performed to sperm using threeDNA concentration of 5, 10 and 20 Î¼g/ml. The incorporation of foreign DNA in sperm andembryos were analyzed using PCR method. Based on PCR analysis, an optimum DNAconcentration for electroporation was 10 Î¼g/ml. Limited number of embryos could bemicroinjected during 20-30 min to reach 2-4 cell stage. Microinjection for 1 second showedhigher survival rate of embryos, although none or very low number of larvae was hatched.Transfast was an effective DNA delivery reagent for humpback grouper sperm. Foreign DNAcould be detected in sperm from two out of ten transfected fish at least 36 hours posttransfection (hpt). By transfection, foreign DNA was detected in sperm at 48 hpt 25 Cincubation temperature. Our study revealed that transfection, microinjection as well aselectroporation could be used as transgenesis methods in humpback grouper. By means ofsimplicity and efficacy, however, electroporationwas an appropriate gene transfermethod.oIn vitroin vivoin vivoin vitro